2017
DOI: 10.1634/theoncologist.2016-0192
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Atypical Femoral Fracture in Metastatic Bone Disease Patients Receiving Denosumab Therapy

Abstract: The incidence of clinical AFF in this context is 0.4% (1/253; 95% confidence interval [CI] 0.1%-2.2%), and the incidence of atypical femoral stress reaction based on imaging review is 4.5% (3/66; 95% CI 1.6%-12.5%). Clinicians should be aware of the clinical prodrome (which may or may not be present) and antecedent imaging changes associated with AFF. 2017;22:438-444 Among patients with metastatic bone disease treated with denosumab, cases of clinical and subclinical atypical femoral fracture (AFF) are rare. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…During a median follow-up of 27 months, they identified one patient with a complete AFF (incidence 0.4%; 95% CI 0.1–2.2%) who received 70 doses of IV BP before receiving 28 monthly doses of denosumab [ 42 ]. They also reviewed all available radiographs in a subset of 66 patients with at least 21 monthly doses of denosumab; two patients had diffuse cortical thickening of the femoral diaphysis and localized periosteal reaction of lateral femoral cortex (incidence 4.5%; 95% CI 1.6–12.5%), confirmed on bone scan and magnetic resonance imaging [ 42 ]. These papers raise concern that clinical and subclinical presentations of AFF may be attributed to metastases and missed in cancer patients.…”
Section: Update On Epidemiologymentioning
confidence: 99%
“…During a median follow-up of 27 months, they identified one patient with a complete AFF (incidence 0.4%; 95% CI 0.1–2.2%) who received 70 doses of IV BP before receiving 28 monthly doses of denosumab [ 42 ]. They also reviewed all available radiographs in a subset of 66 patients with at least 21 monthly doses of denosumab; two patients had diffuse cortical thickening of the femoral diaphysis and localized periosteal reaction of lateral femoral cortex (incidence 4.5%; 95% CI 1.6–12.5%), confirmed on bone scan and magnetic resonance imaging [ 42 ]. These papers raise concern that clinical and subclinical presentations of AFF may be attributed to metastases and missed in cancer patients.…”
Section: Update On Epidemiologymentioning
confidence: 99%
“…On the other hand, no AFF events were recorded in clinical trials of monthly denosumab (120 mg) treatment for patients with bone metastasis, despite the higher and more frequent dosing [6–12]. Although Yang, et al reported one case of clinical AFF in a patient receiving oncologic denosumab therapy from a retrospective review [22], clinical and pathological data are still lacking. We conducted this retrospective multi-center study to assess the incidence of AFF and the clinical and pathological features of patients with bone metastasis treated with denosumab at the dose of 120 mg monthly, and performed a systematic review of articles on this subject that we retrieved from a search of PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the use of denosumab is associated with two particular adverse reactions that, although rare, are of concern in this case. The first is an increased risk of atypical femur fractures mediated by a delay in bone remodelling especially with concomitant glucocorticosteroid use 15. The second is immune dysfunction and an increase in the incidence of infections, mediated by the inhibition of the RANKL/RANK expressed in monocytes and macrophages 14…”
Section: Discussionmentioning
confidence: 99%